PHYSICAL TEST OF LUBRICATING OIL VISCOSITY (KINEMATIC VISCOSITY) AND TBN (TOTAL BASE NUMBER) OF LUBRICATING OIL USING AND WITHOUT USING A CJC TYPE FINE FILTER ON THE MAIN ENGINE KM BINAMA II: Indonesia - Kamal, Mustopa; Ade Hermawan,; Basino, Basino; Priyantini Dewi,; I Ketut Daging,; Faizal Fachruddin, (Journal of Innovation Research and Knowledge, 2024)
This research focuses on the viscosity and Total Base Number (TBN) of lubricating oil in diesel engines. The study tests the characteristics of new lubricating oil, oil used for 500 hours without and with CJC type fine filters, and oil used for 1336.5 hours with CJC fine filters. The testing follows the ASTM D445-21e2 and ASTM D2896-21 methods at the PT PETROLAB SERVICES Laboratory. The results reveal that using CJC fine filters can prolong the life of lubricating oil, as it preserves the quality, particularly within the first 500 working hours. However, beyond 1336.5 hours, some test results become unreasonable, indicating that the oil is no longer suitable for use. To gain a comprehensive understanding of the changes in lubricating oil quality, further testing at 750 and 1000 hours is suggested. Overall, this research highlights the importance of maintaining lubricating oil quality in diesel engines and the potential benefits of using CJC fine filters.